Development and Economy in Educational Building in Greece, Portugal, Spain, Turkey and Yugoslavia : report on the OECD project. - Organisation for Economic Co-operation and Development DEEB Project (Paris : OECD, 1968)
Five Mediterranean countries conducted a 2-year survey of their school building projects to find solutions to the financial, functional, technological, and administrative problems that had arisen in the course of expanding national educational services. This resulting report provides only general recommendations inasmuch as the individual cultural pattern of each country precluded the advancement of one single set of solutions. The three major recommendations were (1) to reduce disparities between working conditions and costs by establishing minimum standards for several educational parameters and by allocating resources accordingly, (2) to allow no construction projects to begin until all financing arrangements have been completed, and (3) to strengthen national coordination between project planning and resource allocation. (Figures 5(1) and 5(2) on pages 58 and 59 may reproduce poorly in hardcopy.) (RA)
Availability: O.E.C.D. Publications Center, Suite 1305, 1750 Pennsylvania Avenue, N.W., Washington, D.C. 20006. (91-68-01-1).
Microfiche.
Keywords: School facilities--Mediterranean region